2020
DOI: 10.1142/s0218625x2030004x
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification by Electro-Discharge Machining Using Powder Metallurgy Electrode: A Review

Abstract: Since the last two decades, many novel techniques have evolved from electro-discharge machining (EDM). Among them, surface modification is one of the rigorously growing technologies by which surface properties can be enhanced by providing a layer having a thickness up to some microns on the workpiece. Existence of tool material on the machined surface after EDM was observed previously. This attribute of EDM makes it a benchmark in surface modification technology. Surface modification in EDM can be done by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…It has considerably affected the surface roughness [27]. The difference between the thermal and electrical conductivity characteristics of the coated electrode material could affect the process of the spark formation and the energy of the generated sparks [22].…”
Section: Effects Of Process Parameters On Ra Using Analysis Of Variance (Anova)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has considerably affected the surface roughness [27]. The difference between the thermal and electrical conductivity characteristics of the coated electrode material could affect the process of the spark formation and the energy of the generated sparks [22].…”
Section: Effects Of Process Parameters On Ra Using Analysis Of Variance (Anova)mentioning
confidence: 99%
“…It was found that I was the most significant influencial parameter. The coated electrode can significantly improve MRR, TWR, Ra and machining accuracy [22]. The roughness of the machined surface with the Cu electrode has been selected to evaluate the effectiveness of coated Cu electrode including silver, nickel, zinc and epoxy.…”
Section: Introductionmentioning
confidence: 99%